Conducting Polymer‐Based Granular Hydrogels for Injectable 3D Cell Scaffolds. Issue 6 (25th April 2021) - Feig, Vivian Rachel; Santhanam, Sruthi; McConnell, Kelly Wu; Liu, Kathy; Azadian, Matine; Brunel, Lucia Giulia; Huang, Zhuojun; Tran, Helen; George, Paul M.; Bao, Zhenan
Abstract: Injectable 3D cell scaffolds possessing both electrical conductivity and native tissue‐level softness would provide a platform to leverage electric fields to manipulate stem cell behavior. Granular hydrogels, which combine jamming‐induced elasticity with repeatable injectability, are versatile materials to easily encapsulate cells to form injectable 3D niches. In this work, it is demonstrated that electrically conductive granular hydrogels can be fabricated via a simple method involving fragmentation of a bulk hydrogel made from the conducting polymer PEDOT:PSS. These granular conductors exhibit excellent shear‐thinning and self‐healing behavior, as well as record‐high electrical conductivity for an injectable 3D scaffold material (≈10 S m −1 ). Their granular microstructure also enables them to easily encapsulate induced pluripotent stem cell (iPSC)‐derived neural progenitor cells, which are viable for at least 5 d within the injectable gel matrices. Finally, gel biocompatibility is demonstrated with minimal observed inflammatory response when injected into a rodent brain. Abstract : Using a simple bulk fragmentation approach, electrically conductive granular hydrogels are fabricated that exhibit record‐high conductivity for an injectable 3D scaffold material. These granular conductive hydrogels are able to encapsulate neural progenitor cells and be injected into a rodent brain with minimal observed inflammatory response.